ANALISIS PROSES PEMBELAJARAN DALAM KONSEP PEMBERDAYAAN KELOMPOK TANI - Dani Ari Setiawan; Endang Sri Redjeki; Zuklarnain Nasution (Graduate School of Universitas Negeri Malang, 2017)
The purpose of this research is analyzing the role of agricultural extension Hall (BPP), analyze the process stages of the occurrence of agricultural learning, and analyze agricultural learning model on a group of farmers. This qualitative research methods are case studies. Data collection techniques: interviews, observation and study of the document. The result is that (1) the existence of the role of agricultural extension officers as education, dissemination of information/innovation facilitators, consultants, supervision, monitors and evaluators, (2) the learning process starts from his protégé participant fedback or, the lesson process, then the output or outputs of learning outcomes to farmers, and (3) learning Models include (a) Airy School Integrated pest control (SLPHT); (b) Pilot planting padi cultivation; (c) guidance techniques; d) exercises and visits; (e) planting synchronously.Tujuan penelitian ini adalah menganalisis peran Balai Penyuluhan Pertanian (BPP), menganalisis proses tahapan terjadinya pembelajaran pertanian, dan menganalisis model pembelajaran pertanian pada kelompok tani. Metode penelitian ini berupa kualitatif studi kasus. Teknik pengumpulan data, meliputi wawancara, observasi, dan studi dokumen. Hasilnya bahwa (1) adanya peran penyuluh pertanian sebagai edukasi, diseminasi informasi/inovasi fasilitator, konsultan, supervisi, pemantau dan evaluator, (2) proses Pembelajaran dimulai dari masukan atau peserta didiknya, proses pembelajarannya, kemudian keluaran dari hasil pembelajaran kepada petani, dan (3) model pembelajaran, meliputi (a) Sekolah Lapang Pengendalian Hama Terpadu (SLPHT); (b) percontohan budidaya tanam padi; (c) bimbingan teknik; (d) Latihan dan Kunjungan (LAKU); (e) tanam serempak.